Light emitting device and method for manufacturing light emitting device

By using a light reflective coating containing plate-like light reflective material, silicon and alkali metal in the light emitting equipment, the shortcomings of existing light emitting equipment in terms of thermal resistance, luminous flux, brightness clarity and brightness difference stability are solved, and the formation of high-performance light reflective coatings and the overall performance improvement of the light emitting equipment are achieved.

JP2025061098AActive Publication Date: 2025-04-10NICHIA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025002743
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2025-01-08
Publication Date
2025-04-10
Estimated Expiration
2041-09-16

AI Technical Summary

Technical Problem

The light reflective coating materials in existing light emitting devices still have room for improvement in improving the performance of light emitting devices, especially in terms of thermal resistance, luminous flux, brightness clarity and brightness difference stability between the light emitting surface and the non-light emitting surface.

Method used

A high-performance light reflective coating is used to form a light reflective coating containing a plate-like light reflective material, silicon and alkali metal. The average particle size of the light reflective material in the coating is 0.6 μm or more to 43 μm or less, and an average longitudinal ratio of 10 or more. A high-performance light reflective coating is formed by mixing and heating.

Benefits of technology

The high-performance light reflective coating of the light emitting device is realized, especially in terms of thermal resistance, and the overall performance and reliability of the light emitting device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061098000001_ABST
    Figure 2025061098000001_ABST
Patent Text Reader

Abstract

To fabricate a light emitting device having a light reflective coating material with high performance.SOLUTION: It has a light emitting element and a light reflective coating material containing plate-shaped light reflecting material 11, silica, and alkali metal to cover the light emitting element, and the average particle size of the light reflective material is equal to or more than 0.6 μm and equal to or more than 43 μm, and the average aspect ratio of the light reflective material is equal to or more than 10.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a light emitting device and a method for manufacturing a light emitting device. [Background technology]

[0002] Some light-emitting devices such as LEDs have a light-emitting element and a light-reflective covering member that covers a part of the light-emitting element. For example, Patent Document 1 discloses a light-reflective covering member in which a reflective material containing a white pigment such as titanium oxide, zinc oxide, tantalum oxide, niobium oxide, zirconia oxide, or aluminum oxide is contained in a base material of a heat-resistant resin such as silicone resin or an inorganic binder. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-216416 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, there is still room for improvement in the light-reflective covering member made of such an inorganic material in order to improve the performance of the light-emitting device. In this specification, the performance of the light-emitting device refers to, for example, heat resistance, luminous flux, brightness, the steepness of the difference in brightness between the light-emitting surface of the light-emitting device and the non-light-emitting surface surrounding the light-emitting surface (partition ability), reliability (life), etc.

[0005] Therefore, an object of the present disclosure is to provide a light emitting device including a light reflective covering member that improves the performance of the light emitting device, in particular, heat resistance, and a method for producing the light emitting device. [Means for solving the problem]

[0006] The light emitting device according to the present disclosure comprises a light emitting element, and a light reflective coating member that contains a plate-shaped light reflector, silica, and an alkali metal and that covers the light emitting element, wherein the light reflector has an average particle size of 0.6 μm or more and 43 μm or less, and the light reflector has an average aspect ratio of 10 or more.

[0007] In addition, the manufacturing method of the light-emitting device according to the present disclosure includes the steps of mixing silica powder, a powder of a plate-shaped light-reflecting material having an average particle size of 0.6 μm or more and 43 μm or less and an average aspect ratio of 10 or more, and an alkaline solution to form a mixture, applying the mixture to a light-emitting element, and heating the mixture to harden it to form a light-reflective coating member. Effect of the Invention

[0008] According to an embodiment of the light emitting device and the method for manufacturing the light emitting device of the present disclosure, it is possible to provide a light emitting device having a light reflective coating member that improves the performance of the light emitting device, in particular its heat resistance, and a method for manufacturing the light emitting device. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view of a light-emitting device according to an embodiment of the present disclosure. [Diagram 2] 2 is an enlarged cross-sectional view of a portion of a light-reflective covering member provided in the light-emitting device shown in FIG. 1. [Diagram 3] 2 is a schematic perspective view of an example of a light reflecting material powder forming a light reflective coating member included in the light emitting device shown in FIG. 1. FIG. [Figure 4A] 2 is a schematic cross-sectional view showing a step of a first method for manufacturing the light emitting device shown in FIG. [Figure 4B] 2 is a schematic cross-sectional view showing a step of a first method for manufacturing the light emitting device shown in FIG. [Figure 4C] 2 is a schematic cross-sectional view showing a step of a first method for manufacturing the light emitting device shown in FIG. [Diagram 5] FIG. 4 is a schematic cross-sectional view showing another step of the first manufacturing method. [Figure 6A]1. FIG. 4 is a schematic cross-sectional view showing a step of a second method for manufacturing the light emitting device shown in FIG. [Figure 6B] 1. FIG. 4 is a schematic cross-sectional view showing a step of a second method for manufacturing the light emitting device shown in FIG. [Figure 6C] 1. FIG. 4 is a schematic cross-sectional view showing a step of a second method for manufacturing the light emitting device shown in FIG. [Figure 6D] 1. FIG. 4 is a schematic cross-sectional view showing a step of a second method for manufacturing the light emitting device shown in FIG. [Figure 7] FIG. 11 is a schematic cross-sectional view of a light-emitting device according to another embodiment of the present disclosure. [Figure 8A] 8A to 8C are schematic cross-sectional views showing an example of a manufacturing process for the light emitting device shown in FIG. [Figure 8B] 8A to 8C are schematic cross-sectional views showing an example of a manufacturing process for the light emitting device shown in FIG. [Figure 8C] 8A to 8C are schematic cross-sectional views showing an example of a manufacturing process for the light emitting device shown in FIG. [Figure 9] 13 is an enlarged cross-sectional view of a portion of the light-emitting device of Example 10 during the manufacturing process. FIG. [Figure 10] 13 is an enlarged cross-sectional view of a portion of a covering member included in the light emitting device according to Example 11. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments and examples for carrying out the present invention will be described with reference to the drawings. Note that the light emitting device and the manufacturing method for the light emitting device described below are intended to embody the technical concept of the present invention, and unless otherwise specified, the present invention is not limited to the following. In each drawing, components having the same function may be given the same symbol. In consideration of the explanation or ease of understanding of the main points, the embodiments and examples may be shown separately for convenience, but partial replacement or combination of the configurations shown in different embodiments and examples is possible. In the embodiments and examples described below, descriptions of matters common to the above will be omitted, and only the differences will be described. In particular, similar effects due to similar configurations will not be mentioned in each embodiment or example. The size and positional relationship of the components shown in each drawing may be exaggerated to clarify the explanation.

[0011] EMBODIMENT 1 A light emitting device 1 according to this embodiment includes a light emitting element 4, a light transmissive member 6, and a light reflective covering member 5 that covers the light emitting element 4, as shown in FIG. The light emitting element 4 includes a semiconductor laminate 2 and a pair of electrodes 3 provided on the lower surface of the semiconductor laminate 2 . The light-transmitting member 6 is disposed to cover the upper surface 4a of the light-emitting element 4. A part of the surface of the light-transmitting member 6 is exposed from the covering member 5, and the surface of the light-transmitting member 6 exposed from the covering member 5 includes the light emission surface 1a of the light-emitting device 1. The covering member 5 is disposed so as to cover part of the side and bottom surfaces of the light-emitting element 4 and part of the side and bottom surfaces of the light-transmitting member 6. The covering member 5 contains a plate-shaped light reflecting material 11, silica, and an alkali metal. The light reflecting material 11 has an average particle size of 0.6 μm or more and 43 μm or less, and an average aspect ratio of 10 or more.

[0012] (Light emitting element) The semiconductor laminate 2 included in the light emitting element 4 includes, for example, an n-type semiconductor layer, a p-type semiconductor layer, and a light emitting portion disposed between the n-type semiconductor layer and the p-type semiconductor layer. The light emitting element 4 includes a growth substrate 7 (for example, a sapphire substrate) for growing a semiconductor layer on the surface of the semiconductor laminate 2 opposite to the surface on which the electrode 3 is formed. However, the growth substrate may be removed after the semiconductor layer is formed. The peak wavelength of the light emitted by the semiconductor laminate 2 is, for example, in the range of 260 nm to 630 nm. The light emitting element 4 emits, for example, ultraviolet light or blue light. The pair of electrodes 3 provided on the lower surface of the semiconductor laminate 2 are a p-electrode and an n-electrode. In the growth substrate 7, the width of the growth substrate 7 (the length of the longest side of the polygonal growth substrate 7 when viewed from above) is preferably 2.5 to 3.5 times the thickness of the growth substrate 7. With such a relationship between the thickness and width of the growth substrate 7, the light extraction efficiency from the light emitting element 4 is improved.

[0013] (Translucent member) The light-transmitting member 6 may contain a resin or may be an inorganic material. If the light-transmitting member 6 is an inorganic material, it has higher heat resistance than a light-transmitting member containing a resin, so that a light-emitting device with high heat resistance can be manufactured. For example, glass can be used as an inorganic material. The light-transmitting member 6 can contain a wavelength conversion material such as a phosphor. When the light-transmitting member 6 is an inorganic material containing a phosphor in its base material, for example, YAG (yttrium aluminum garnet) can be used as the phosphor, and alumina or silica can be used as the base material. Note that the light-transmitting member 6 does not need to contain a wavelength conversion material. In this case, the light from the light-emitting element is emitted to the outside without being wavelength-converted.

[0014] (Covering material) In this embodiment, the covering member 5 covers the light emitting element 4 and the light transmissive member 6 by exposing the lower surface 3a of the electrode 3 of the light emitting element 4 and the upper surface 6a of the light transmissive member 6. Here, "covering" includes not only a state in which the covering member 5 is arranged in contact with the light emitting element 4 and / or the light transmissive member 5, but also a state in which the covering member 5 is arranged between the light emitting element 4 and / or the light transmissive member 5 and another member or space (e.g., an air layer) is interposed between the covering member 5 and the light emitting element 4. In this specification, expressions such as "cover", "covered", and "covered" also include a state similar to "covering". In addition, when another member or space (e.g., an air layer) is arranged between the side surface of the light emitting element 4 and the covering member 5, the inner surface of the covering member 5 facing the side surface of the light emitting element 4 can have an inclined surface that moves away from the side surface of the light emitting element 4 as it moves from the lower surface to the upper surface in a cross-sectional view. This inclined surface may be, for example, linear or curved in a cross-sectional view. The upper surface 6a of the light-transmitting member 6 exposed from the covering member 5 is the light emission surface 1a of the light-emitting device 1. However, the light-transmitting member 6 is not an essential component of the light-emitting device 1 according to this embodiment. When the light-transmitting member 6 is not provided, the covering member 5 is disposed, for example, so that the upper surface 4a of the light-emitting element 4 and the lower surface 3a of the electrode 3 are exposed. In this case, the upper surface 4a of the light-emitting element 4 is the light emission surface.

[0015] The covering member 5 is a mixture of a plurality of inorganic materials. The covering member 5 includes a light reflecting material 11 and a supporting member 12 that supports the light reflecting material 11. The supporting member 12 includes silica and an alkali metal. As described below, the covering member 5 is formed through a heating process in which a mixture of a powder of the light reflecting material 11, a powder of silica, and an alkaline solution is heated. The covering member 5 may be composed only of an inorganic material, or may be composed mainly of an inorganic material. Here, the covering member 5 is used as a member that covers the light-emitting element 4 and the light-transmitting member 6, but it can be used for other purposes. The covering member 5 according to this embodiment can be used, for example, as a light reflecting layer disposed on the surface of a mounting substrate to reflect light traveling from the light-emitting element to the mounting substrate. The mixture 50 according to this embodiment can be used not only as a material for the covering member 5, but also as a material that constitutes a reflecting wall disposed to surround the light-emitting element in an LED package.

[0016] (light reflective material) The powder of the light reflecting material 11 is a plate-like particle having two opposing main surfaces 11a, 11b, as shown in Fig. 3, for example. The two opposing main surfaces 11a, 11b of the light reflecting material 11 can also be called the upper and lower surfaces of the light reflecting material 11. The powder of the light reflecting material 11 can also be called scale-like particles. Note that Fig. 3 is merely a schematic diagram showing the powder of the light reflecting material 11 as, for example, a thin cylinder, in order to facilitate the explanation of the shape of the powder of the light reflecting material 11. The light reflecting material 11 is, for example, boron nitride or alumina, which is capable of reflecting light of the peak wavelength from the light emitting element.

[0017] The light reflecting material 11 may be primary particles, or may be secondary particles formed by agglomeration of two or more primary particles, or may be a mixture of primary particles and secondary particles.

[0018] The average aspect ratio of the light reflecting material 11 is 10 or more, and preferably 10 to 70. The average aspect ratio of the light reflecting material 11 is calculated by the following method.

[0019] <How to calculate the average aspect ratio> The average aspect ratio of the light reflecting material 11 is calculated by measuring the thickness and width of the light reflecting material 11 included in the covering member 5 in the cross section of the light emitting device 1. First, a cross section passing through the center of the light emitting surface 1a of the light emitting device 1 and substantially perpendicular to the light emitting surface 1a is exposed. The cross section is exposed by cutting the light emitting device 1.

[0020] Next, the exposed cross section is mirror-polished. The mirror-polished cross section is photographed with a scanning electron microscope (SEM), the cross section of the light reflecting material 11 is extracted, and a measurement area including approximately 1000 cross sections of the light reflecting material 11 is selected. The number of pixels of the microscope is set to approximately 20 million pixels, and the magnification is set to 500 times to 3000 times. In addition, in this specification, the cross section of the light reflecting material 11 is a surface that is approximately perpendicular to one main surface 11a and / or the other main surface 11b of the light reflecting material 11. Due to their shape, the plate-like light reflecting material 11 tends to be arranged in the covering member 5 so that the main surfaces 11a or 11b face each other and overlap each other. Therefore, by appropriately selecting the cross section of the light emitting device 1 to be exposed, the cross section of the light reflecting material 11 can be appropriately extracted by the SEM.

[0021] Next, the width (length in the longitudinal direction of the cross section of the light reflecting material) and thickness (length in the lateral direction of the cross section of the light reflecting material) of each cross section of the extracted light reflecting material 11 are measured one by one using image analysis software, and the average value of the width relative to the thickness is calculated. The average value of the measured values ​​of 100 light reflecting materials 11 is then taken as the average aspect ratio. When the light reflecting material 11 is boron nitride, the average aspect ratio of the light reflecting material 11 is, for example, 16.5 or more and 19.2 or less. When the light reflecting material 11 is alumina, the average aspect ratio of the light reflecting material 11 is, for example, 10 or more and 70 or less.

[0022] The average particle size of the light reflecting material 11 is not less than 0.6 μm and not more than 43 μm. Here, the fusion of the powder of light reflecting material 11 and the powder of silica by the heating process and the elution of the powder of light reflecting material 11 into the alkaline solution by the heating process are slight. Therefore, the shape and size of the powder of light reflecting material 11 are substantially the same as the shape and size of the light reflecting material 11 contained in the covering member 5 formed through the heating process. Therefore, the average particle size of the light reflecting material 11 is calculated by measuring the particle size of the powder of light reflecting material 11 by the following method.

[0023] <How to calculate average particle size> The particle size of the powder of the light reflecting material 11 is calculated, for example, using a scanning electron microscope "TM3030Plus" manufactured by Hitachi High-Technologies Corporation. First, one side of a double-sided tape made of carbon is attached to the sample stage of the microscope, and then the powder of the light reflecting material 11 is placed on the other side of the double-sided tape. The number of pixels of the microscope is set to 1.23 million pixels, and the magnification is set to 1000 times to 2000 times, and images of 100 powders (particles) of the light reflecting material 11 are obtained. Then, the particle size of each particle is measured by image analysis software. In this specification, the particle size of the powder of the light reflecting material 11 is the maximum diameter among the diameters when viewed from the main surface 11a or 11b of the light reflecting material 11. Next, the median diameter of the measured particles is calculated, and the calculated value is the average particle size of the light reflecting material 11. The particle size of the powder of the light reflecting material 11 may be calculated by extracting a cross section of the covering member by SEM and measuring it by image analysis software.

[0024] When the light reflecting material 11 is boron nitride, the average particle size of the light reflecting material 11 is, for example, 6 μm or more and 43 μm or less When the light reflecting material 11 is alumina, the average particle size of the light reflecting material 11 is, for example, 0.6 μm or more and 10 μm or less.

[0025] (silica) The ratio of the silica and light reflecting material 11 contained in the covering member 5 is, for example, 1:4 or more and 1:1 or less in weight ratio. That is, the weight of the light reflecting material 11 contained in the covering member 5 is, for example, 1 time or more and 4 times or less than the weight of the silica contained in the covering member 5. Within this range, it is possible to reduce the shrinkage of the mixture when it is cured. If the amount of the light reflecting material is too large, there is a risk that the curability will decrease. On the other hand, if the amount of silica is too large, there is a risk that the shrinkage due to curing will be large and cracks will occur during curing. The average particle size of the silica is, for example, from 0.1 μm to 10 μm. Within this range, the density per volume of the raw materials (light reflecting material and silica) can be improved, so that the strength of the coating member can be ensured. The average particle size of the silica powder is preferably smaller than the average particle size of the light reflecting material. This allows the silica powder to fill the gaps that are formed between the light reflecting materials when mixed. The average particle size of the silica powder is calculated by measuring the particle size distribution of the silica powder using a laser diffraction method. The average particle size of the silica is a value measured before mixing with the alkaline solution. This is because the silica powder melts when mixed with the alkaline solution, making it difficult to confirm the particle size from the coating member 5. In addition, in order to calculate the content ratio of silica and the light reflecting material from the coating member, for example, a cross section of the coating member extracted by SEM may be observed and calculated based on the occupancy rate of silica and the light reflecting material.

[0026] (alkali metals) The alkali metal is the alkali metal contained in the above-mentioned alkaline solution. The alkali metal is, for example, potassium and / or sodium.

[0027] The light reflecting material 11 having the above average particle size and average aspect ratio functions as aggregate for the covering member 5 when the covering member 5 is heated by heat generated from the light emitting element 4. This suppresses the contraction of the covering member 5 due to the heat of the light emitting element 4, and a light emitting device 1 with high heat resistance can be obtained. Such a light emitting device 1 has a long service life. In addition, the covering member 5 can reflect light from the light emitting element by utilizing the difference in refractive index between the light reflecting material and silica. Furthermore, by obtaining the covering member 5 in which the shrinkage caused by the heat of the light emitting element 4 is suppressed in this way, the light emitting device 1 can be used even under conditions where the heat generated by the light emitting element is large (for example, when the amount of power supplied to the light emitting element is large). By increasing the amount of power supplied to the light emitting element, the amount of light per light emitting device can be increased. In addition, since the amount of light energy possessed by the light emitting element is larger than that of the light emitting element emitting visible light, and the resin is easily photodegraded, the light emitting element may be mounted in a ceramic package that is highly durable against light energy. However, by using the covering member 5 according to this embodiment, it is possible to provide a light emitting device in which the light emitting element emitting ultraviolet light is covered with the covering member 5 without using a ceramic package. The light emitting device including the covering member 5 in this way can reduce the manufacturing cost and can be made smaller than a light emitting device including a ceramic package.

[0028] The coefficient of linear terminal expansion of covering member 5 is preferably 0.0.5 ppm / °C or more and 5 ppm / °C or less in the temperature range of 40°C to 300°C. This makes it possible to suppress the expansion of covering member 5 even if the temperature of covering member 5 rises during use of the light emitting device, thereby improving reliability. In this embodiment, the coefficient of linear terminal expansion of covering member 5 is about 1 ppm.

[0029] Furthermore, it is preferable that the covering member 5 contains a scattering material. The scattering material is, for example, mainly zirconia or titania. When the light emitting element emits ultraviolet light, zirconia, which has low light absorption in the ultraviolet wavelength region, is preferable. When the covering member 5 contains a scattering material, the light reflectance of the covering member 5 is improved. This makes the difference in luminance between the light emitting surface of the light emitting device 1 and the covering member 5 (non-light emitting surface) surrounding the light emitting surface steep. In other words, the visibility at the light emitting surface 1a of the light emitting device 1 is improved.

[0030] The light scattering material may be titania alone, or titania whose surface has been subjected to various surface treatments such as silica, alumina, zirconia, zinc, or an organic material. The light scattering material may be zirconia alone, or zirconia that has been subjected to various surface treatments such as silica, alumina, zinc, organic, etc. Also, stabilized zirconia with added calcium, magnesium, yttrium, aluminum, etc., or partially stabilized zirconia may be used.

[0031] When a scattering material is added to the coating member, the scattering material is present in a dispersed state in the silica.

[0032] The average particle size of the scattering material is desirably smaller than that of the light reflecting material 11. As a result, the scattering material is disposed in the gaps between the light reflecting materials 11, and thus the light emitted from the light emitting element 4 is prevented from being emitted outside the light emitting device 1 through the gaps between the light reflecting materials 11. As a result, the parting at the light emitting surface 1a of the light emitting device 1 is improved. The average particle size of the scattering material is measured by a laser diffraction method.

[0033] In the first embodiment, a light emitting device including the light-transmitting member 6 has been described, but a light emitting device not including the light-transmitting member 6 may be used. In a light emitting device including the light-transmitting member 6 as in the first embodiment, the upper surface of the light-transmitting member 6 and the upper surface of the covering member 5 are flush with each other. In contrast, in a light emitting device not including the light-transmitting member 6, the upper surface of the light emitting element and the upper surface of the covering member are flush with each other.

[0034] Manufacturing method <First manufacturing method> Next, an example (first manufacturing method) of a method for manufacturing the light emitting device 1 according to this embodiment will be described with reference to FIGS. 4A to 4C.

[0035] (Process for mounting light-emitting element on mounting board) First, a plurality of light-emitting elements 4 are prepared, each having a light-transmitting member 6 disposed on its upper surface 4a. The light-transmitting member contains a phosphor. Next, the light-emitting elements 4 are mounted on a mounting substrate 20 at predetermined intervals, as shown in FIG. 4A.

[0036] (A process for mixing a light reflecting material powder, a silica powder, and an alkaline solution to form a mixture) Next, a mixed powder obtained by mixing the powder of the light reflecting material 11 and the powder of silica is mixed with an alkaline solution to prepare a mixture 50. The mixed powder and the alkaline solution are mixed, for example, until a uniform viscosity is obtained, and then degassed and stirred using a stirring and degassing machine capable of stirring under reduced pressure. The powder of the light reflecting material 11 has an average particle size of 0.6 μm or more and 43 μm or less, and an average aspect ratio of 10 or more, preferably 10 or more and 70 or less. The powder of the light reflecting material 11 is, for example, boron nitride powder or alumina powder. The silica powder has an average particle size of, for example, 0.1 μm or more and 10 μm or less. The concentration of the alkaline solution is, for example, 1 mol / L or more and 5 mol / L or less. If the concentration of the alkaline solution is too low, the curing property is deteriorated, and there is a possibility that the strength of the covering member 5 may decrease or the coating member 5 may decompose. On the other hand, if the concentration of the alkaline solution is too high, there is a possibility that excess alkali metal may precipitate, and the reliability of the light-emitting element may decrease. The alkaline solution is, for example, a potassium hydroxide solution or a sodium hydroxide solution. The silica powder and the light reflecting material 11 powder are mixed in a weight ratio of, for example, 1:4 or more and 1:1 or less. That is, the silica powder and the light reflecting material 11 powder are mixed in a weight ratio of, for example, 1 time or more and 4 times or less of the silica powder. The alkaline solution and the mixed powder are mixed in a weight ratio of, for example, 2:10 or more and 8:10 or less. That is, the alkaline solution and the mixed powder are mixed in a weight ratio of, for example, 1.25 times or more and 5 times or less of the alkaline solution. If the amount of alkaline solution is too small, multiple fine lumps are formed when mixed, making molding difficult. On the other hand, if the amount of alkaline solution is too large, cracks may occur during hardening, or the strength of the hardened coating member may decrease.

[0037] Furthermore, when a scattering material is to be contained in the covering member 5 of the light emitting device 1 to be manufactured, the scattering material is mixed into this mixture 50. The average particle size of the scattering material is, for example, smaller than the average particle size of the powder of the light reflecting material 11. The scattering material mainly contains, for example, zirconia or titania.

[0038] (Step of applying the mixture to the light-emitting element) In this step, the mixture 50 is applied to at least the side surface of the light emitting element 4. In this manufacturing method for producing the light emitting device 1, as shown in FIG. 4B, the mixture 50 is applied to the mounting substrate 20 so as to cover the light emitting element 4 and the light-transmitting member 6. It is preferable to vibrate the mounting substrate 20 during and / or after the mixture 50 is applied to the mounting substrate 20. This allows the mixture 50 to be easily spread over a wide area. In the case of a light emitting device that does not have the light-transmitting member 6, in this step, the mixture 50 may be placed on the mounting substrate 20 so as to cover only the light emitting element 4. Instead of vibrating the mounting substrate, the mixture 50 may be applied while being vibrated.

[0039] Furthermore, before applying the mixture 50, a protective film can be formed on the electrode 3 and / or the wiring electrode of the mounting substrate 20. This can prevent the electrode 3 and / or the wiring electrode of the mounting substrate 20 from being damaged, such as corroded, by the alkaline solution contained in the mixture 50. Furthermore, by providing a protective film on the electrode 3 and / or the wiring electrode of the mounting substrate 20, damage caused by corrosive gases in the atmosphere can be prevented while the manufactured light emitting device 1 is in use. In other words, the gas barrier properties of the light emitting device 1 can be improved. The above-mentioned protective film can be formed by using atomic layer deposition (ALD). Furthermore, the protective film may be applied to the electrode 3 and / or the wiring electrode of the mounting substrate 20 after applying the mixture 50, or may be applied before and after applying the mixture 50. By applying a protective film to the electrode 3 and / or the wiring electrode of the mounting substrate 20 before and after applying the mixture 50, the gas barrier property of the light emitting device 1 can be further improved.

[0040] Furthermore, after the mixture 50 is placed on the mounting substrate 20, the mixture can be pressed using, for example, a glass plate to form the upper surface of the mixture 50 into a flat shape. In this manner, by pressing and flattening the upper surface of the mixture 50, in the light-emitting device 1 produced, among the light-reflecting materials contained in the covering member 5, the light-reflecting materials 11 located in the vicinity region R1 (see FIG. 9) of the light-emitting element 4 and the light-transmitting member 6 are arranged at an angle of 0° or more and 45° or less from the surfaces of the light-emitting element 4 and the light-transmitting member 6. The arrangement state of the light-reflecting materials 11 will be demonstrated in the examples described later. The vicinity region R1 (see FIG. 9) is, for example, a region within a range of 10 μm from the surfaces of the light-emitting element 4 and the light-transmitting member 6. Furthermore, if the surfaces of the light-emitting element 4 and / or the light-transmitting member 6 are not flat, a surface obtained by averaging the unevenness of the surface is regarded as the plane of the light-transmitting member. In this way, when the light reflecting material 11 located in the vicinity region R1 is arranged at an angle of 0° or more and 45° or less from the surfaces of the light emitting element 4 and the light-transmitting member 6, the light reflecting materials 11 can be arranged in close proximity with their main surfaces 11a, 11b facing each other. That is, the density of the light reflecting material 11 in the vicinity region R1 can be increased. Therefore, when the light reflecting material 11 is a highly heat-conductive material such as boron nitride or alumina, the dissipation of heat generated from the light emitting element 4 and the light-transmitting member 6 can be promoted.

[0041] Furthermore, before applying the mixture 50, a film of silica or alumina can be formed on the mounting substrate 20. This improves the adhesive strength between the mounting substrate 20 and the mixture 50.

[0042] (A step of heating the mixture to form a light-reflective coating member / heating step) Next, the mixture 50 is heated and cured to form the light-reflective coating member 5. This process includes a provisional curing process in which the mixture 50 is cured at a first temperature T1, and a full curing process in which the mixture 50 is cured at a second temperature T2 higher than the first temperature T1. The provisional curing process is performed, for example, at a first temperature T1 of 80° C. to 100° C. for 10 minutes to 2 hours. The full curing process is performed, for example, at a second temperature T2 of 150° C. to 250° C. for 10 minutes to 3 hours. By carrying out the provisional curing step at a temperature lower than that of the main curing step before the main curing step in this manner, cracks are less likely to occur in the resulting covering member 5. Furthermore, by performing the provisional curing step and the main curing step under pressure, the light reflectance of the formed coating member 5 is increased. This is believed to be because the mixture is pressurized, and the light reflecting material in the mixture is cured in a state where it is more densely arranged. The pressure applied during the main curing step is, for example, 1 MPa.

[0043] (Step of exposing the light-transmitting member) 4C, the covering member 5 is ground to expose the upper surface 6a of the light-transmitting member 6. The upper surface 6a of the light-transmitting member 6 exposed at this time becomes the light emission surface 1a of the light emitting device 1.

[0044] (Singulation process) Next, the light emitting device 1 is obtained by dividing the substrate 1 into individual pieces along a predetermined cutting position CL, each of which includes one light emitting element 4. The division is performed using, for example, a blade.

[0045] In the first manufacturing method, in the step of applying the mixture, the mixture 50 is applied to cover the upper surface 6a of the light-transmitting member 6, and in the subsequent step of exposing the light-transmitting member, the upper surface 6a of the light-transmitting member 6 is exposed. However, in the step of applying the mixture, the upper surface 6a of the light-transmitting member 6 may be exposed and the mixture 50 may be disposed on the mounting substrate 20. This makes it possible to omit the step of exposing the light-transmitting member.

[0046] In this way, in the step of applying the mixture, when the upper surface 6a of the light-transmitting member 6 is exposed and the mixture 50 is applied, it is preferable to form a groove 90 in the mixture 50 as shown in FIG. 5 after the step of applying the mixture and before the heating step. It is preferable that the groove 90 is arranged along the cutting position CL in the singulation step. It is also preferable that the covering member is divided by forming the groove 90. As a result, the contraction stress generated during curing is directed from the groove cutting position toward the light-emitting element 4, so that it is possible to prevent the light-emitting element 4 and the mixture 50 from peeling off during curing. As a result, it is possible to increase the adhesive strength between the covering member 5 formed by curing the mixture 50 and the light-emitting element 4. The groove cutting is performed using, for example, a blade.

[0047] As described above, in the singulation process, singulation is performed so that one light emitting device includes one light emitting element. However, this is not limited to this, and singulation can also be performed so that one light emitting device includes two or more light emitting elements. The same applies to the second manufacturing method described below.

[0048] <Second manufacturing method> Next, with reference to FIGS. 6A to 6D, another example of a method for manufacturing the light emitting device 1 according to this embodiment will be described. The second manufacturing method will be described.

[0049] (A step of preparing a mixture 50 by mixing a light reflecting material powder, a silica powder, and an alkaline solution) A mixed powder of the light reflecting material 11 powder and silica powder is mixed with an alkaline solution to prepare a mixture 50. This process is similar to the process of forming the mixture 50 by mixing the light reflecting material powder, silica powder, and an alkaline solution in the first manufacturing method.

[0050] (Step of preparing a light-transmitting member on the side of which the mixture 50 is to be placed) As shown in FIG. 6A, a light-transmitting member 6 having a mixture 50 disposed on its side surface is prepared. The light-transmitting member 6 having a mixture 50 disposed on its side surface can be produced, for example, as follows. First, one or more through holes are provided in the prepared layered mixture 50, and a layered mixture 50 having through holes is formed. When a plurality of through holes are provided, it is desirable that the plurality of through holes are provided at a predetermined interval. Next, the light-transmitting member 6 is disposed in the through hole. In this way, the light-transmitting member 6 having a mixture 50 disposed on its side surface can be produced. The light-transmitting member may or may not include a wavelength conversion member (e.g., a phosphor). The mixture 50 disposed on the side surface of the light-transmitting member 6 may be heated at this stage, or may be heated after the mixture 50 is coated on the light-emitting element 4, which will be described later. The through holes may be formed by punching after the layered mixture 50 is formed.

[0051] (Step of placing light emitting element on first light transmissive member) 6B, the multiple light-emitting elements 4 are placed so that their upper surfaces 4a are in contact with the light-transmitting member 6. In this case, the surface of the light-emitting element 4 opposite to the surface on which the electrodes are formed is referred to as the upper surface 4a. Also, the surface of the light-transmitting member 6 opposite to the surface on the light-emitting element side is referred to as the upper surface 6a.

[0052] (Step of applying the mixture to the light-emitting element) Next, as shown in Fig. 6C, the mixture 50 is applied onto the layer of the mixture 50 so as to cover the light emitting element 4. As in the first manufacturing method, in this manufacturing method, it is preferable to vibrate the mounting substrate during and / or after application of the mixture 50. Also, as in the first manufacturing method, in this manufacturing method, a protective film may be disposed on the surface of the electrode 3 by atomic layer deposition modeling before and / or after application of the mixture 50.

[0053] (A step of heating the mixture to form a light-reflective coating member / heating step) Next, the mixture 50 is heated and cured to form the covering member 5. This step is similar to the step (heating step) of heating the mixture to form a light-reflective covering member in the first production method.

[0054] (Step of exposing electrodes) 6D, the covering member 5 is ground to expose the lower surface 3a of the electrode 3 of the light emitting element 4. Note that, here, the surface of the electrode 3 opposite to the surface on the light emitting element 4 side is referred to as the lower surface 3a.

[0055] (Singulation process) Next, the light emitting device 1 is obtained by dividing the substrate 1 into individual pieces along a predetermined cutting position CL, each of which includes one light emitting element 4. The division is performed using, for example, a blade.

[0056] Here, an example has been described in which the mixture 50 is disposed on the side surface of the light-transmitting member 6, but instead of the mixture 50, a white resin containing titanium oxide may be disposed.

[0057] <Other embodiments and their manufacturing methods> In the light emitting device 1 according to the first embodiment, the upper surface 6a of the light-transmitting member 6 is exposed from the covering member 5, and the upper surface of the light emitting device 1 includes the upper surface 6a of the light-transmitting member 6 and the upper surface of the covering member 5, but is not limited thereto. For example, as shown in FIG. 7, the upper surface 106a and the side surface 106b of the light-transmitting member 106 are exposed from the covering member 5, and the upper surface of the light emitting device 100 may be only the upper surface 106a of the light-transmitting member 106. The upper surface 106a of the light-transmitting member 106 is the light emission surface 100a of the light emitting device 100. The light-transmitting member 106 may or may not include a wavelength conversion member (e.g., a phosphor).

[0058] Such a light emitting device 100 is manufactured by the following manufacturing method. 8A, a plurality of light-emitting elements 4 are placed on a light-transmitting sheet 60 at predetermined intervals. The light-emitting elements 4 are placed on the light-transmitting sheet 60 such that the upper surfaces of the light-emitting elements 4 face the light-transmitting sheet 60. 8B, the mixture 50 is placed on the light-transmitting sheet 60 so as to cover the light-emitting element 4. Thereafter, the mixture 50 is heated to form a light-reflective covering member 5. This step is performed in the same manner as the step (heating step) of heating the mixture to form a light-reflective covering member in the first and second manufacturing methods. 8C, the lower surface 3a of the electrode 3 is exposed and the electrode 3 is cut into individual pieces along the predetermined cutting positions CL, thereby completing the manufacture of the light emitting device 100. In this embodiment, a metal film can be disposed on each of the exposed lower surfaces 3a of the pair of electrodes 3. At this time, it is preferable that the metal film is disposed so as to cover not only the lower surface 3a of the electrode 3, but also the lower surface of the covering member 5 around the lower surface 3a. In other words, it is preferable that the metal film is disposed so that the area of ​​the lower surface of the metal film is larger than the area of ​​the exposed lower surface 3a of the electrode 3. This improves the electrical connection between the light emitting device 1 and the wiring board. Furthermore, when the electrode 3 contains Cu and is configured to be exposed, there is a risk of a mounting failure occurring when mounting on the wiring board due to oxidation of Cu, but such a risk does not occur because the electrode 3 is covered with a metal film that is less likely to be oxidized than Cu. As such a metal film, a film in which Ni, Ru, and Au are laminated in this order from the electrode 3 side can be used. If the outermost surface is Au, it is less likely to be oxidized than Cu, so that the oxidation of the metal film can be suppressed. Furthermore, by using Ni as the metal that bonds with the electrode 3 in the metal film, the adhesion between the electrode 3 and the metal film can be improved. The metal film can be formed, for example, as follows: A metal film is sputtered onto the lower surface 3a of the electrode 3 and the lower surface of the covering member, and the metal film is removed by laser ablation so that the pair of electrodes 3 are electrically separated.

[0059] Examples and Reference Examples Examples and Reference Examples will be described below. In Reference Example 1, Reference Example 2, and Examples 1 to 9, coated members were produced and the shrinkage retention rates were measured when the coated members were heated for 1 hour at 1000° C. The amount of alkaline solution added was appropriately adjusted to provide a viscosity suitable for molding.

[0060] A coated member 5 of Reference Example 1 was produced as follows. First, a powder of light reflecting material 11 having an average particle size of 1 μm and an average aspect ratio of 4.6 was mixed with a powder of silica having an average particle size of 0.4 μm in median diameter to prepare a mixed powder. The powder of light reflecting material 11 was a powder of boron nitride. The powder of silica and the powder of boron nitride were mixed in a weight ratio of 4:5. The mixed powder was mixed with an alkaline solution having a concentration of 3 mol / L to prepare a mixture. The alkaline solution was a potassium hydroxide solution. The alkaline solution and the mixed powder were mixed in a weight ratio of 5.8:9. Next, the mixture 50 was heated at a first temperature of 90° C. under a pressure of 1 MPa for 1 hour to be provisionally cured. Next, the mixture 50 was heated at a second temperature of 200° C. under a pressure of 1 MPa for 2 hours to be fully cured, thereby producing the coated member 5 .

[0061] The coating members 5 of Reference Example 2 and Examples 1 to 9 were prepared by changing the material of the light-reflecting material, the average particle size of the light-reflecting material, the aspect ratio of the light-reflecting material, and the weight ratio of the silica powder to the light-reflecting material as shown in Table 1, and were prepared in the same manner as in Reference Example 1 except for the conditions shown in Table 1.

[0062] The coated members 5 of Reference Example 1, Reference Example 2, and Examples 1 to 9 were divided into two plates having a diameter of about 3 cm and a thickness of about 1 mm, and one of the two coated members was heated at 1000° C. for one hour. Thereafter, the ratio of the length of one side of the divided cross section of the heated coated member to the length of one side of the divided cross section of the unheated coated member was calculated (shrinkage retention rate). The results are shown in Table 1.

[0063] [Table 1]

[0064] From the results of Reference Example 1, Reference Example 2, and Examples 1 to 9, the shrinkage maintenance rates of Examples 1 to 9 were 99.00% or more, which was greater than the shrinkage maintenance rates of Reference Examples 1 and 2. Therefore, it was revealed that covering members 5 of Examples 1 to 9, which contain silica, an alkali metal, and a light reflecting material having an average particle size of 0.6 μm or more and 43 μm or less and an aspect ratio of 10 or more, have high heat resistance.

[0065] In Examples 10 to 13, light emitting devices including a covering member 5 were fabricated, and the luminous flux, light emitting surface brightness, parting property, and reliability of each were evaluated. In Example 10, the cross section was observed when the covering member 5 applied to the light emitting element 4 was pressed. In Example 11, the cross section of the fabricated light emitting device was observed by SEM.

[0066] Example 10 The light emitting device of Example 10 was fabricated as follows. A light-emitting element having a plate-shaped light-transmitting member 6 containing YAG bonded thereto was placed on an adhesive sheet with the light-transmitting member 6 facing the adhesive sheet. The light-emitting element 4 had a rectangular shape of 1 mm×1 mm in top view, and a peak wavelength of 450 nm to 455 nm. The light-emitting element 4 was placed on the adhesive sheet at a pitch of 1.8 mm in both the X and Y directions (width direction and depth direction). A heat-resistant sheet based on polyimide was used as the adhesive sheet, but other materials may be used as long as the adhesive sheet has heat resistance above the provisional curing temperature. The light-transmitting member 6 had a rectangular shape of 1.1 mm×1.1 mm in top view, and a thickness of 180 um. The light-emitting element 4 had a thickness of 200 um. The electrode 3 of the light-emitting element 4 contained Cu with a height of about 50 um. A mixed powder was prepared by mixing boron nitride with an average particle size of 10 um and an average aspect ratio of approximately 17 with silica with an average particle size of 0.4 um in a weight ratio of 1:1. Then, 3.4 g of 3 mol / L potassium hydroxide solution was added to 10 g of the prepared mixed powder, and the mixture was mixed using a stirring rod, and then degassed and stirred using a stirring and degassing machine capable of stirring under reduced pressure, to obtain a white, uniform, viscous mixture 50. The obtained mixture 50 was applied so as to cover the light emitting element 4 and the light-transmitting member 6. Thereafter, the mixture 50 was pressed using a glass plate to form the mixture 50 into a flat shape with a thickness of approximately 1 mm. Fig. 9 shows a cross section passing through the center of the upper surface 6a of the light-transmitting member 6 at this time and substantially perpendicular to the upper surface 6a. As shown in Fig. 9, of the light-reflecting materials 11 contained in the mixture 50, the light-reflecting materials 11 located near the light-emitting element 4 and the light-transmitting member 6 tend to be arranged such that the longitudinal direction of the light-reflecting material 11 forms an angle of 0° or more and 45° or less with respect to the sides of the light-emitting element 4 and the light-transmitting member 6. It is believed that such an arrangement tendency was achieved by increasing the aspect ratio of the plate-shaped light-reflecting material 11 and slowing down the flow speed of the mixture 50 flowing near the light-emitting element 4 and the light-transmitting member 6 when the mixture 50 is applied to the light-emitting element 4. Next, the mixture 50 was heated and cured to obtain a light-reflective coating member 5. As for the curing conditions, a pressurized oven was used to perform temporary curing for 60 minutes in a pressurized nitrogen atmosphere of 1 MPa. After the sheet was peeled off, the pressurized oven was used again to perform main curing for 40 minutes in a pressurized nitrogen atmosphere of 1 MPa. The temperature during main curing was 200°C. Next, the covering member 5 was ground to expose the electrode 3. Finally, the substrate was cut into individual pieces using a blade having a thickness of 100 μm. After cutting into individual pieces, a light-emitting device was obtained that emitted white light and had a rectangular shape of 1.7 mm×1.7 mm when viewed from above and a thickness of about 0.4 mm.

[0067] Example 11 The light emitting device of Example 11 was fabricated as follows. A light-emitting device was obtained in the same manner as in Example 10, except that 4 g of 3 mol / L potassium hydroxide solution was added to 13 g of powder material obtained by mixing boron nitride with an average particle size of 10 um and an average aspect ratio of approximately 17, silica with an average particle size of 0.4 um, and titania with an average particle size of 0.25 um in a weight ratio of 5:5:3. A cross section of this light emitting device was observed by SEM. Fig. 10 shows a part of the covering member 5 in a cross section passing through the center of the upper surface 6a of the light-transmitting member 6 and substantially perpendicular to the upper surface 6a. Fig. 10 clearly shows that voids 13 exist in the covering member 5, and a part of the voids 13 is in contact with the light reflecting material 11. In this way, by locally generating the voids 13, there is an effect of suppressing the shrinkage of the covering member 5 when it is heat-cured. Furthermore, in the light emitting device according to this embodiment, by adding titania as scattering material 14, it was possible to realize improvements in reflectance and light blocking properties compared to those in which titania was not added.

[0068] Example 12 The light emitting device of Example 12 was fabricated as follows. A light-emitting device was obtained in the same manner as in Example 10, except that 4.8 g of 3 mol / L potassium hydroxide solution was added to 14 g of powder material prepared by mixing boron nitride with an average particle size of 10 μm and an average aspect ratio of approximately 17, silica with an average particle size of 0.4 μm, and zirconia in a weight ratio of 5:5:4. The light emitting device according to this embodiment can improve the reflectance and light blocking properties by adding zirconia as a scattering material, compared to the device without zirconia. In particular, since zirconia has low absorption and good reflectance properties in the wavelength range of 250 nm to 420 nm, which is the wavelength range of light emitting elements that emit ultraviolet light, the properties of the light emitting device that emits ultraviolet light are improved.

[0069] The light emitting devices of Examples 10 to 12 prepared as described above were compared and evaluated for luminous flux, light emitting surface brightness, visibility, and reliability. <Luminous flux> The light emitting devices of Examples 10 to 12 were evaluated for luminous flux using an integrating sphere. The light emitting device of Example 10 had a luminous flux of 161 [lm]. The light emitting device of Example 11 had a luminous flux of 162 [lm]. The light emitting device of Example 12 had a luminous flux of 162 [lm]. The forward current supplied to the light emitting devices of Examples 10 to 12 was 350 [mA].

[0070] <Light-emitting surface brightness> When a light emitting device is used in combination with an optical system such as a lens, the brightness of a specific light emitting area (in the present disclosure, the light exit surface of the translucent member) is important. For the light emitting devices of Examples 10 to 12, the brightness of the exit surface (exposed surface) of the translucent member 6 was evaluated using a two-dimensional color luminance meter manufactured by Radiant Vision Systems. The brightness of the light emitting device of Example 10 was 33.7 [cd / cm 2 The luminance of the light-emitting device of Example 11 was 37.3 [cd / cm 2 The luminance of the light-emitting device of Example 12 was 35.8 [cd / cm 2 The forward current supplied to the light emitting devices of Examples 10 to 12 was 350 [mA].

[0071] <Dismissibility> In car headlights and the like, safety standards are applied to light components leaking outside the light-emitting area, so a reduction in light components outside the light-emitting area (visibility) is required. When the value obtained by dividing the luminance of light leaking from the light-transmitting member covering member by the average luminance of light emitted from the light-transmitting member 6 is used as an index of visibility, the values ​​obtained were 7.2% in Example 10, 2.2% in Example 11, and 3.6% in Example 12. The light leaking from the covering member is light measured at a point 125 um away from the boundary point between the light-transmitting member and the covering member when viewed from above.

[0072] <Reliability> A 1000-hour life test was carried out on the light-emitting devices of Examples 11 and 12 by applying a current of 1.5 A in a high-temperature environment of 85° C. The junction temperature during operation was approximately 175° C. The "junction temperature" refers to the temperature of the active layer, which is the region that emits light from the light-emitting element. When a current of 700 mA was applied, the output maintenance rate after 1000 hours was 102% of the initial value for the light emitting device of Example 11, and 101% for the light emitting device of Example 12. In addition, for the light emitting device of Example 11 and the light emitting device of Example 12, the occurrence and progression of cracks was not confirmed during the test.

[0073] Example 13 The light emitting device of Example 13 was fabricated as follows. Light-emitting elements 4, each having a peak wavelength of 280 nm and a rectangular shape of 1 mm x 1 mm when viewed from above, were arranged on an adhesive polyimide sheet at a pitch of 2.2 mm with the sapphire substrate side facing the sheet. The thickness of the light-emitting element 4 was 700 μm. The electrode 3 of the light-emitting element 4 included an Au bump with a height of about 30 um. To 10 g of a mixed powder made by mixing boron nitride with an average particle size of 10.5 μm and an average aspect ratio of 16.5 with silica with an average particle size of 0.4 μm in a weight ratio of 1:1, 3 g of 3 mol / L potassium hydroxide solution was added and mixed in a container. After that, the mixture was further kneaded in a vacuum mixing and defoaming machine to obtain mixture 50. The obtained mixture 50 was applied so as to cover the light emitting element 4 and the light-transmitting member 6. Thereafter, the mixture 50 was pressed using a glass plate and formed into a flat shape with a thickness of approximately 2 mm. Next, a temporary curing was performed in the atmosphere for 60 minutes using an oven. The temperature during the temporary curing was 95°C. After that, the polyimide adhesive sheet that had been holding the light-emitting element 4 was peeled off. After the sheet was peeled off, a full curing was performed in a N2 atmosphere of 1 MPa using a pressurized oven for 40 minutes. The temperature during the full curing was 200°C. Next, the covering member 5 was ground to expose the electrode 3. Finally, the substrate was cut into individual pieces using a blade having a thickness of 100 μm. After cutting into individual pieces, a light-emitting device was obtained that emitted ultraviolet light and had a rectangular shape of 2.1 mm×2.1 mm when viewed from above and a thickness of approximately 720 μm.

[0074] <Reliability> A reliability test was carried out on the light emitting device manufactured as described above. A life test was carried out for 1000 hours at a room temperature of 25°C with a current of 500mA applied. The junction temperature during operation was approximately 100°C. When a current of 350 mA was applied, the output retention rate after 1000 hours was 92% of the initial value. No deterioration such as discoloration or cracks was observed in the appearance after the test.

[0075] The above describes the embodiments, modifications, examples, and reference examples of the present disclosure, but the disclosed contents may vary in details of the configuration, and changes in the combination and order of elements in the embodiments, modifications, examples, and reference examples may be realized without departing from the scope and concept of the present disclosure as claimed. [Explanation of symbols]

[0076] 1, 100 Light emitting device 1a, 100a Light emitting surface 2 Semiconductor laminate 3 Electrode 3a Lower surface 4 Light emitting element 4a upper surface 5 covering member 6, 106 light-transmitting member 6a, 106a Top surface 7 Growth substrate 106b Side 11 Light reflective material 11a, 11b Principal surface 12 Support member 13 Void 14 Scattering material 20 Mounting substrate 50 Mixture 60 Light-transmitting sheet 90 Groove

Claims

1. A light-emitting element; a light-reflective coating member that contains a plate-shaped light-reflecting material, silica, and an alkali metal and that covers the light-emitting element; The average particle size of the light reflecting material is 0.6 μm or more and 43 μm or less, A light emitting device, wherein the average aspect ratio of the light reflecting material is 10 or more.

2. the light reflecting material is boron nitride; The light emitting device according to claim 1 , wherein the average particle diameter of the light reflecting material is not less than 6 μm and not more than 43 μm.

3. the light reflecting material is alumina; The light emitting device according to claim 1 , wherein the average particle diameter of the light reflecting material is 0.6 μm or more and 10 μm or less.

4. 4. The light emitting device according to claim 1, wherein a content ratio of said silica to said light reflecting material is 1:4 or more and 1:1 or less by weight.

5. The light emitting device according to any one of claims 1 to 4, wherein the alkali metal is potassium or sodium.

6. The light emitting device according to claim 1 , wherein the covering member includes a scattering material.

7. The light emitting device according to claim 6 , wherein an average particle size of the scattering material is smaller than an average particle size of the light reflecting material.

8. 8. The light emitting device according to claim 6 or 7, wherein the scattering material is mainly zirconia or titania.

9. a light-transmitting member is disposed on the light-emitting element, and a portion of a surface of the light-transmitting member is exposed from the covering member; 9. The light emitting device according to claim 1, wherein a surface of said light-transmitting member that is exposed from said covering member includes a light exit surface.

10. The light emitting device according to claim 9 , wherein the light transmissive member is made of an inorganic material.

11. 11. The light emitting device according to claim 1, wherein the light emitting element emits ultraviolet light.

12. 12. The light emitting device according to claim 1, wherein the covering member has a linear thermal expansion coefficient of 0.5 ppm / .degree. C. or more and 5 ppm / .degree. C. or less in a temperature range of 40.degree. C. to 300.degree.

13. A step of mixing silica powder, a powder of a plate-shaped light reflecting material having an average particle size of 0.6 μm or more and 43 μm or less and an average aspect ratio of 10 or more, and an alkaline solution to form a mixture; applying the mixture to a light emitting device; and heating the mixture to harden it and form a light-reflective covering member.

14. The step of forming a light-reflective covering member includes: a pre-curing step of curing the mixture at a first temperature; The method for manufacturing a light emitting device according to claim 13 , further comprising: a main curing step of curing the mixture at a second temperature higher than the first temperature.

15. 15. The method for manufacturing a light emitting device according to claim 13, wherein in the step of forming the mixture, the silica powder and the light reflecting material powder are mixed at a weight ratio in the range of 1:4 or more and 1:1 or less.

16. The method for manufacturing a light emitting device according to any one of claims 13 to 15, wherein in the step of forming the mixture, a weight ratio of the alkaline solution to the silica powder and the light reflecting material powder is 2:10 or more and 8:10 or less.

17. The method for manufacturing a light emitting device according to any one of claims 13 to 16, wherein the alkaline solution used in the step of forming the mixture has a concentration of 1 mol / L or more and 5 mol / L or less.

18. The method for manufacturing a light emitting device according to any one of claims 13 to 17, wherein the light reflecting material is boron nitride or alumina in the step of forming the mixture.

19. 19. The method for manufacturing a light-emitting device according to claim 13, wherein the alkaline solution used in the step of forming the mixture is a potassium hydroxide solution or a sodium hydroxide solution.

20. The method for manufacturing a light emitting device according to any one of claims 13 to 19, further comprising the step of mixing a scattering material into the mixture.

21. The method for manufacturing a light emitting device according to claim 20 , wherein in the step of mixing a scattering material with the mixture, the scattering material has an average particle size smaller than an average particle size of the powder of the light reflecting material.

22. The method for manufacturing a light emitting device according to claim 20 or 21, wherein the scattering material is mainly zirconia or titania in the step of mixing the mixture with the scattering material.

Citation Information

Patent Citations

  • Light-emitting device

    JP2010238846A

  • Light emitting device

    JP2013251504A

  • Coated phosphorescent material and light-emitting device containing the same

    JP2014519540A

  • Light emitting device

    JP2015026871A

  • Semiconductor light emitting device and method of measuring the same

    JP2014216416A